ECONOMIC RESILIENCE IN ASYMMETRIC WARFARE - Guntur Eko Saputro; Suwito Suwito (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Economic Resilience is a dynamic condition of the nation's economic life that contains tenacity and resilience that contains the ability to develop national strength in facing and overcoming all threats, obstacles, disturbances, obstacles, and challenges originating from abroad and from within the country. Asymmetric war is a war that involves two or more actors through a broad battlefield that includes Trigatra (geography, demography, and natural resources) and Pancagatra (ideology, political economy, socio-culture, and defense and security). The purpose of the research is to provide government input on the importance of economic resilience in the face of asymmetric war. This study uses the Strategy Theory written by Clausewitz which views several things related to the elements of war, namely Means, Way, and End. Research with qualitative methods is aimed at understanding social phenomena from the participant's perspective. The result of this study is economic resilience needs strengthening in the digital economy, digital bureaucracy and banking strengthening